Implementasi Sistem Proteksi Arus dan Tegangan Lebih pada PLTS 10x100 Wp - Djulihenanto , Saddani; Saputra, Masramdhani; Hermawan, Satria Luthfi; Akbar, Divac Nabiel; Gumilang, Binar Surya; Putri, Amala Wicaksana (Elposys: Jurnal Sistem Kelistrikan, 2025)
The increasing adoption of solar power systems has highlighted the need for effective overcurrent and overvoltage protection to ensure operational reliability and safety. This study aimed to implement and evaluate a protection system for a 10 × 100 Wp solar power plant at PPYD Al-Ikhlas, Singosari, Indonesia. The research employed an experimental approach, including testing Miniature Circuit Breakers (MCBs), Surge Protection Devices (SPDs), and grounding systems. MCBs were evaluated using an injection current tester to assess their tripping characteristics, while SPDs were tested for continuity using a multimeter. The grounding system was examined with an earth tester to measure its resistance before and after implementing a parallel electrode configuration. The results indicated that the installed protection system significantly enhanced safety, with MCBs effectively disconnecting excessive currents as per IEC 60898-1 standards. The SPD successfully mitigated transient voltage surges, and the grounding system reduced resistance below 5 Ω, complying with PUIL 2020 standards. These findings support previous studies on electrical protection and grounding efficiency, emphasizing the need for tailored solutions in small-scale solar systems. Future research should explore real-time monitoring with IoT-based systems and optimize grounding configurations for high-resistivity soils. The proposed protection approach contributes to enhancing the resilience of distributed solar power installations.